Tiametoxam nas características histológicas de raízes jovens de cana-de-açúcar - Martins, Raphael Gonçalves; Gonçalves Martins, Maria Bernadete [UNESP]; Silva, João Marcelo; Pereira, Marcelo Andrade; Appezzato-da-Glória, Beatriz; e Castro, Paulo Roberto de Camargo (FapUNIFESP (SciELO), 2012)
Thiamethoxam is a systemic insecticide from the neonicotinoid group, nitroguanidin family which affects the nicotinic receptor acetyl choline in the insect membrane, wounding the nervous system and causing the death of the insect. It was used with success in the control of initial pests of several crops. It was considered that thiamethoxam has a bioactivator effect, because in the absence of insects promoted increase in vigor, development and productivity of crops. This work was carried out to verify if thiamethoxam causes histological changes in sugarcane roots. In this work, it was used optical microscopy, images arrest, tissue biometrics and statistical analysis, in young roots of sugarcane RB 83 5486 after the treatments with different thiamethoxam concentrations. It was determined changes in histological structure of tissues 7, 14, 21 and 28 days after the treatments, establishing its effects on root plant anatomy. It was verified that thiamethoxam increased root cortex width, increasing the vascular cylinder and the metaxylem vessel elements number in the vascular tissue until 21 days after application.
Thiamethoxam on the histological characteristics of sugarcane young roots
Keywords: Anatomy; Root system; Saccharum spp.